Flow Boiling Pressure Drop Characteristics in Rectangular Channels under Uniform and Non-Uniform Heating. (August 2020) - Sun, Rulei; Song, Gongle; Zhang, Dalin; Su, G.H.; Kulacki, F.A.; Tian, Wenxi
Highlights: Measurements of two-phase flow boiling pressure drop in a rectangular channel are reported. The thermal-hydraulic parameters analysis of pressure drop gradient are studied. The existing homogeneous, separated and empirically fitted correlations are evaluated using the experimental data. A new correlation based on the form of Muller-Steinhagen-Heck formula is proposed. The lateral power distribution has an important influence on the flow boiling pressure drop. ABSTRACT: Pressure drop characteristics in flow boiling in a vertical rectangular channel (2.0 mm × 60 mm × 1000 mm) are reported under uniform and non-uniform transverse wall heating. The test section has symmetrical wall power, and the effective heating area is 56 mm × 700 mm. A wide range of operating conditions is obtained by varying the inlet pressure and mass flow. Results show that the variation of the pressure drop gradients with thermal parameters is similar under uniform and non-uniform wall heating. The pressure drop gradient decreases as the saturation pressure increases and increases significantly as the mass flow rate increases. It remains nearly constant or slightly decreases with increasing vapor quality at low mass flux, while it decreases slightly first and then rises rapidly at high mass flux. The homogeneous flow model using the equivalent viscosity assumption significantly underestimates experimental values, and the data dispersion is relatively large. The Beattie-Whalley correlation has a relatively good prediction, with a weighted mean absolute percent error (WMAPE) of 24.6%. The Muller-Steinhagen-Heck and Li-Wu correlations are found to be the best with WMAPE of 11.1% and 12.2% respectively, and most of the predicted values are within a ±20% error band. A new correlation based on the forms of Muller-Steinhagen-Heck correlation is proposed, the Bond number is introduced, and measurements are within ±8% of predictions. The lateral power distribution has an important influence on the flow boiling pressure drop, which can be attributed to the effects of void distribution and transverse flow. The non-uniform wall power distributions increase the pressure drop gradient compared to that of the uniform distribution.